Robot hands and multi-fingered haptic interfaces : fundamentals and applications - Kawasaki, Haruhisa, 1949- (World Scientific, 2015)
Robot Hands and Multi-Fingered Haptic Interfaces is a monograph focusing on the comparison of human hands with robot hands, the fundamentals behind designing and creating the latter, and robotics' latest advancements in haptic technology. This work discusses the design of robot hands; contact models at grasping; kinematic models of constraint; dynamic models of the multi-fingered hand; the stability theorem of non-linear control systems; robot hand control; design and control of multi-fingered haptic interfaces; application systems using multi-fingered haptic interfaces; and telecontrol of robot hands using a multi-fingered haptic interface. Robot Hands and Multi-Fingered Haptic Interfaces is intended mainly for readers who have a foundation in basic robot arm engineering. To understand robot hand manipulation, readers must study kinematic constraint models of fingers, hand dynamics with constraints, stability theorems of non-linear control, and multi-fingered hand control - this book will benefit readers' understanding of this full range of issues regarding robot hand manipulation.
Keywords: Robot hands.; Haptic devices.; elektronické knihy; electronic books